2019
DOI: 10.1016/j.chemosphere.2018.11.077
|View full text |Cite
|
Sign up to set email alerts
|

A novel combination of bioelectrochemical system with peroxymonosulfate oxidation for enhanced azo dye degradation and MnFe2O4 catalyst regeneration

Abstract: MnFe 2 O 4 catalyzed PMS oxidation driven by MFCs was established. Complete degradation of Orange II was achieved in the MFC-MnFe 2 O 4 / PMS system. Electricity was recovered in the MFC-MnFe 2 O 4 /PMS system during dye degradation. ≡Mn 2þ and ≡Fe 2þ was regenerated via cathode reduction of ≡Mn 3þ and ≡Fe 3þ .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…However, when the composite amount further increased to 0.8 g/L, the removal percentage declined from 95.4 ± 3.0% to 84.6 ± 2.1%, which may be explained by the excess catalyst causing ineffective PMS consumption (Guan et al, 2013). This finding was consistent with our previous study, in which the amount of MnFe 2 O 4 affected the generation efficiency of SO 4 À in the MnFe 2 O 4 /PMS system and a further rise in the amount of MnFe 2 O 4 adversely influenced SO 4 À generation (Xu et al, 2019). These results indicated that the optimal Co 3 O 4 loading amount on BC and the optimal Co 3 O 4 -BC composite amount were 10 wt% and 0.2 g/L, respectively.…”
Section: Influential Factors On the Catalytic Activity Of Co 3 O 4 -Bcsupporting
confidence: 92%
“…However, when the composite amount further increased to 0.8 g/L, the removal percentage declined from 95.4 ± 3.0% to 84.6 ± 2.1%, which may be explained by the excess catalyst causing ineffective PMS consumption (Guan et al, 2013). This finding was consistent with our previous study, in which the amount of MnFe 2 O 4 affected the generation efficiency of SO 4 À in the MnFe 2 O 4 /PMS system and a further rise in the amount of MnFe 2 O 4 adversely influenced SO 4 À generation (Xu et al, 2019). These results indicated that the optimal Co 3 O 4 loading amount on BC and the optimal Co 3 O 4 -BC composite amount were 10 wt% and 0.2 g/L, respectively.…”
Section: Influential Factors On the Catalytic Activity Of Co 3 O 4 -Bcsupporting
confidence: 92%
“…Meanwhile, the lattice absorption of Fe-O detected in the recovered MnFe 2 O 4 /BGA composite was blue-shifted, indicative of the change in its chemical environment after reusing 4 times. Such blue shift might be due to the effect of Verway hopping (Mn 2+ + Fe 3+ →Mn 3+ + Fe 2+ ) [ 41 ], which leads to the increase in electron cloud density around iron ions. Thus, both the emerged weak bands and the strengthening in the lattice absorption of Fe-O were not results of the change in material structure of the MnFe 2 O 4 /BGA composite.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the lattice absorption of Fe-O detected in the recovered MnFe2O4/BGA composite was blue-shifted, indicative of the change in its chemical environment after reusing 4 times. Such blue shift might be due to the effect of Verway hopping (Mn 2+ + Fe 3+ →Mn 3+ + Fe 2+ ) [41], which leads to the increase in electron cloud density around iron ions. Thus,…”
Section: Stability and Reusability Of The Mnfe2o4/bga Compositementioning
confidence: 99%
“…The nanoparticles used to improve the anode serve as a bridge for electron transfer between the bacteria and the anode. Due to the availability of active sites for bacterial growth on the anode, this leads to an increase in the rates of electricity generation [ 67 ].…”
Section: The Anodementioning
confidence: 99%